Radio echo sounding (RES) surveys of the lower terminus of Taku Glacier, Alaska, 2014-2016 - Jenna Zechmann; Jason Amundson; Martin Truffer (Arctic Data Center, 2018)
Between 2014 and 2016, radio echo sounding (RES) surveys of the lower terminus of Taku Glacier were performed to obtain a glacier bed geometry to be used primarily to calculate subglacial erosion rates from past RES and bathymetric surveys of the area. Our project performed RES surveys during several different field campaigns, using two different methods: 1) point radar soundings, and 2) radar profiles.